2020
DOI: 10.1007/s10570-020-03170-1
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the fatigue behaviour of cellulose/polyolefin composites using photo-chemical fibre surface modification bio-inspired by natural role models

Abstract: Based on the knowledge that plant structures often have graded stiffness transitions between strengthening elements and the surrounding matrix, which result in good damping behaviour and high toughness of the plant structure, the fatigue behaviour of composites made from rayon fibre and polypropylene (PP) as a matrix could be enhanced by photochemical surface modification of the regenerated cellulose fibres. The surface modification was achieved by deposition of UV-polymerized organic thin layers using pentaer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Kenaf fiber composites treated with 35 wt.% alkali-silane (4% concentration) sustained an average of 64% more fatigue cycles to fracture at 45% of their UTS than untreated composites. A similar finding was reported by Muessig et al [89], who promoted the bonding between regenerated cellulose fibers and polypropylene matrix via photochemical surface modification of the fiber. Composites with 1% pentaerythritol triacrylate treated regenerated cellulose fibers exhibited an approximately 18% increase in fatigue strength at one million cycles compared to untreated composites.…”
Section: Towards Improving Fatiguesupporting
confidence: 87%
“…Kenaf fiber composites treated with 35 wt.% alkali-silane (4% concentration) sustained an average of 64% more fatigue cycles to fracture at 45% of their UTS than untreated composites. A similar finding was reported by Muessig et al [89], who promoted the bonding between regenerated cellulose fibers and polypropylene matrix via photochemical surface modification of the fiber. Composites with 1% pentaerythritol triacrylate treated regenerated cellulose fibers exhibited an approximately 18% increase in fatigue strength at one million cycles compared to untreated composites.…”
Section: Towards Improving Fatiguesupporting
confidence: 87%
“…Plastics derived from petroleum are widely used in numerous application-based industries in day-to-day activities. Various plasticizers and antimicrobial agents are added to bio-nanocomposite films are added to F I G U R E 9 SEM image of (A) unidirectional specimen, (B) processed image of a specific area [54] All these surface treatment methods reported noticeable reversed fatigue lives and fatigue strength improvements [68] (ii) Silane surface treatment The treatment reported an improved fatigue performance than acid surface treatments [69] (iii) Photochemical fiber surface modification The treatment reported an increase in the affinity of fibers towards non-polar substances resulting in enhanced adhesion between the fiber and the matrix, which promoted fatigue performance than its untreated counterparts [67] Increased requirement of hydrophilicity in composites for packing applications [66] The application-based requirement reported poor fatigue performance due to a decrease in the affinity of fibers towards non-polar substances [67] Improved requirement of surface wetting leading to a notable biocompatibility improvement of materials and applicational functionality of antimicrobial need [67] The application-based requirement reported weak adhesion between the fiber and the matrix resulting in poor fatigue performance [67] Nanocomposite coating for applications in the fields of optical, medical, and dental sciences…”
Section: Effect Of Plasticizers and Antimicrobial Agentsmentioning
confidence: 99%
“…The fatigue performance depends on (i) the effect of the nanofiller concentration and the (ii) control of the secondary structure [67] (such as variation in the microstructure of the protein promoted by post-treatments that induce transition in the secondary structure of the silk [70][71][72] improve their characterization. Pankaj Jha added plasticizers such as glycerol and sorbitol and antifungal agents such as potassium sorbate and grapefruit seed extract to corn starch-chitosan bio-nanocomposite films.…”
Section: Effect Of Plasticizers and Antimicrobial Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 It has the advantages of being cheap, light, easy to process and durable, therefore, it has become a potential substitute of traditional materials such as wood, metal and glass, for many aspects of modern human life. 2 Especially, numerous studies have been investigated to improve the mechanical, thermal, and functional properties of intrinsic polyolefin by compositing micro and nano scale fillers such as montmorillonite, [3][4][5][6] cellulose, [7][8][9][10] carbon fiber, [11][12][13][14] graphene [15][16][17] and molybdenum disulfide. 18,19 These studies have shown that micro and nano scale fillers can improve many physical and some mechanical properties of polymer, including reducing wear rate and friction significantly.…”
Section: Introductionmentioning
confidence: 99%